Radioprotection in Dentistry: knowledge and practices (Research, Society and Development, 2021)
The present study aimed to identify the knowledge and attitudes of dental surgeons regarding the guidelines contained in Ordinance SVS/MS No. 453, dated June 1, 1998, in force until the year 2019 and later replaced with Collegiate Board Resolution (RDC) No. 330/19. Our objective was to identify the practices of professionals working in the dental field regarding the knowledge of the essential criteria for performing periapical, interproximal, panoramic, cephalometric or even cone beam computed tomography imaging exams. The research tool was a questionnaire consisting of 45 questions based on Administrative Rule 453/98, which addresses the requirements for the organization and operation of diagnostic radiology services. The questionnaire was sent to 150 dentists via institutional e-mail, and only 55 professionals returned it. The responses revealed that 64% of the dentists declared not to be aware of the guidelines of ordinance 453/98 and 49.1% did not know the basic principles of radioprotection. Regarding the norms related to the environment, including the use of a chronometer, thermometer and time-temperature table, the study revealed that 83.6% of the interviewees did not use such equipment and that 74.5% of them were not aware of the technical details ofthe equipment. Regarding radiographic films, 64.5% answered that they did not know their sensitivity, and 25.5% did not use them as a protective barrier during the exams. Finally, the study revealed that the professional practices adopted by dental surgeons are insufficient to meet the principle contained in ordinance 453/98 and in the RDC 330/19, regarding the exposure of patients to a radiation dose.